Preliminary Considerations of an Inflation Targeting Framework for the Philippines - Lim, G.; Debelle, Guy. (Washington, D.C. : International Monetary Fund, 1998)
Monetary policy in the Philippines has had multiple objectives. Moreover, shifts in money demand and the money multiplier have made base money a less reliable anchor for monetary policy. Hence, on present policies, a steady reduction in inflation is not assured, and changes to the monetary policy framework should be considered. This paper reviews the benefits as well as the constraints of an inflation targeting framework and the necessary preconditions--both in terms of the institutional infrastructure and the appropriate inflation target--for its successful implementation, including the ability to forecast inflation reasonably well over policy-relevant time horizons.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet